Pengenalan Aplikasi “Chanting” (Alat Puja Bakti) Berbasis Android di Vihara Giri Bhakti Kabupaten Pesawaran - Sidartha Adi Gautama; Susanto; Rina manggalani; Wayan Sunando Gautama (Jurnal Pengabdian dan Pengembangan Inovasi kepada Masyarakat (PENAMAS), 2023)
This community service activity aims to improve the competence of educators and education by utilizing Android application-based chanting in the district Buddhist Sunday School Pesawaran so that activities in education can be carried out properly. The target of dedication is the Giri Bhakti Monastery, with a total of 50 participants. Service activities are carried out using various methods, ranging from surveys, focus group discussions, demonstrations, performances, and mentoring. The material training provided includes an introduction to the "Chanting" Application (a pujja bhakti tool) Based on Android. The results of community service activities show success, with indications of high enthusiasm and motivation to utilize the participant's Android application-based chanting at each stage of training activities.